SOME FUNDAMENTAL PROPERTIES OF HEAPS - Mahanani, Dwi Mifta; Ismiarti, Dewi (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
Heap is defined to be a non-empty set with ternary operation satisfying associativity, that is for every and satisfying Mal’cev identity, that is for all . There is a connection between heaps and groups. From a given heap, we can construct some groups and vice versa. The binary operation of groups can be built by choosing any fixed element of heap and is defined by =[x,e,y] for any . Otherwise, for given a binary operation of group , we can make a ternary operation defined by for every On heaps, there are some notions which are inspired by groups, such as sub-heaps, normal sub-heaps, quotient heaps, and heap morphisms. On this study, we will associate sub-heaps and corresponding subgroups and discuss some properties of heap morphisms.